Evaluating the Incapacitative Benefits of Incarcerating Drug Offenders in Los Angeles and Maricopa (Arizona) Counties, 1986 and 1990 - Cohen, Jacqueline ([Verlag nicht ermittelbar], 1996)
The objective of this study was to examine the observable offending patterns of recent and past drug offenders to assess the crime control potential associated with recent increases in the incarceration of drug offenders. The periods examined were 1986 (representing the second half of the 1980s, when dramatic shifts toward increasing incarceration of drug offenders first became evident), and 1990 (after escalating sentences were well under way). Convicted offenders were the focus, since these cases are most directly affected by changes in imprisonment policies, particularly provisions for mandatory prison terms. Offending patterns of convicted and imprisoned drug offenders were contrasted to patterns of convicted robbers and burglars, both in and out of prison. The researchers used data from the National Judicial Reporting Program (NJRP), sponsored by the U.S. Department of Justice, Bureau of Justice Statistics (BJS), for information on the court processing of individual felony convictions. The National Association of Criminal Justice Planners (NACJP), which maintains data for the approximately 50 counties included in the NJRP, was contracted to determine the counties to be sampled (Los Angeles County and Maricopa County in Arizona were chosen) and to provide individual criminal histories. Variables include number of arrests for robbery, violent crimes, property crimes, and other felonies, number of drug arrests, number of misdemeanor arrests, rate of violent, property, robbery, weapons, other felony, drug, and misdemeanor arrests, offense type (drug trafficking, drug possession, robbery, and burglary), total number of incarcerations, total number of convictions, whether sentenced to prison, jail, or probation, incarceration sentence in months, sex, race, and age at sampled conviction, and age at first arrest (starting at age 17).